The Use of Unmanned Aerial Vehicles in Environmental Education - Lisnik, Anton; Parczewski, Rafał (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article substantiates the urgency of the problem of ecology, environmental protection, development of environmental awareness of the world population. Environmental education is a process that should be implemented at each level of education. It is proved that public awareness of environmental protection is an important element in the process of globalization. The increasing amount of waste caused also by the COVID-19 pandemic creates many threats to the environment. The authors believe that continuous increasing of human awareness is possible by means of staff, teachers, vocational training, and the various information campaigns implementation. The use of unmanned aerial vehicles can support activities conducted by schools or other educational institutions dealing with ecological issues in Poland. Through specialized functionalities, drones can effectively show the existing threats to the natural environment. This type of activity may contribute to the visualization of pollution, fires, floods, or other dangerous environmental phenomena. It is emphasized that photos or videos data can be used in the general education system. The possibilities of primary and general secondary education in the formation of ecological knowledge and skills of children and youth are determined. The analysis of the content of the curriculum for Polish schools, including lessons in geography, biology, technology, chemistry, ethics, basics of entrepreneurship, and others, on their environmental orientation was carried out. Emphasis is placed on the necessity to improve teachers’ skills, their non-formal education by means of environmental seminars, training, workshops, etc.